Cartography and art - Cartwright, William (Springer, 2017)
This book is the fruition of work from contributors to the Art and Cartography: Cartography and Art symposium held in Vienna in February 2008. This meeting brought together cartographers who were interested in the design and aesthetics elements of cartography and artists who use maps as the basis for their art or who incorporate place and space in their expressions. The outcome of bringing together these like minds culminated in a wonderful event, spanning three evenings and two days in the Austrian capital. Papers, exhi- tions and installations provided a forum for appreciating the endeavors of artists and cartographers and their representations of geography. As well as indulging in an expansive and expressive occasion attendees were able to re? ect on their own work and discuss similar elements in each other’s work. It also allowed cartographers and artists to discuss the potential for collaboration in future research and development. To recognise the signi? cance of this event, paper authors were invited to further develop their work and contribute chapters to this book. We believe that this book marks both a signi? cant occasion in Vienna and a starting point for future collabo- tive efforts between artists and cartographers. The editors would like to acknowledge the work of Manuela Schmidt and Felix Ortag, who undertook the task of the design and layout of the chapters.